Molecular basis of African yam domestication: analyses of selection point to root development, starch biosynthesis, and photosynthesis related genes - Roland Akakpo; Nora Scarcelli; Hana Chaïr; Alexandre Dansi; Gustave Djedatin; Anne-Céline Thuillet; Bénédicte Rhoné; Olivier François; Karine Alix; Yves Vigouroux (BMC Genomics, 2017)
Abstract Background After cereals, root and tuber crops are the main source of starch in the human diet. Starch biosynthesis was certainly a significant target for selection during the domestication of these crops. But domestication of these root and tubers crops is also associated with gigantism of storage organs and changes of habitat. Results We studied here, the molecular basis of domestication in African yam, Dioscorea rotundata. The genomic diversity in the cultivated species is roughly 30% less important than its wild relatives. Two percent of all the genes studied showed evidences of selection. Two genes associated with the earliest stages of starch biosynthesis and storage, the sucrose synthase 4 and the sucrose-phosphate synthase 1 showed evidence of selection. An adventitious root development gene, a SCARECROW-LIKE gene was also selected during yam domestication. Significant selection for genes associated with photosynthesis and phototropism were associated with wild to cultivated change of habitat. If the wild species grow as vines in the shade of their tree tutors, cultivated yam grows in full light in open fields. Conclusions Major rewiring of aerial development and adaptation for efficient photosynthesis in full light characterized yam domestication.